Improving spatial predictability of petroleum resources within the Central Tertiary Basin, Spitsbergen: a geochemical and petrographic study of coals from the eastern and western coalfields - Uguna, Jacob Onyebuolise; Carr, Andrew D.; Marshall, Chris; Large, David J.; Meredith, Will; Jochmann, Malte; Snape, Colin E.; Vane, Christopher H.; Jensen, Maria A.; Olaussen, Snorre (Elsevier, 2017)
Central Tertiary Basin (CTB) coals from a variety of palaeogeographic conditions within the Longyear and Verkhnij seams, were sampled to assess the relationship between the petroleum present, the remaining generation potential and coal geochemistry in order to improve the spatial predictability of petroleum resources within the basin. Vitrinite reflectance (VR) values from the CTB coals have been shown to be suppressed (Marshall et al., 2015a). This study attempts to quantify and correct for this suppression effect by applying the Lo (1993) method (LoVR), which uses Hydrogen Index (HI) values to modify VR data, and the coal Rank(Sr) scale of Suggate (2000, 2002), a technique not affected by suppression. In addition, the oil generation and expulsion thresholds for the CTB coals were investigated.